Potentials of Digital Beamforming in Bi- and Multistatic SAR - Krieger, Gerhard; Moreira, Alberto (IEEE Geoscience and Remote Sensing Symposium, 2003)
Digital beamforming on receive is an innovative concept to gather additional information about the direction of scattered radar echoes during the acquisition of synthetic aperture radar (SAR) images. This additional information can be used to suppress range and azimuth ambiguities, to improve geometric and/or radiometric resolution, and to increase the unambiguous swath width. It is shown that this technique is especially promising in combination with bistatic SAR constellations, where digital beamforming on the receive will allow for more compact antenna structures. Furthermore, an extension of digital beamforming to multistatic SAR formations will enable a reduced antenna aperture for each receiver, thereby allowing cost-effective and powerful SAR missions with wide swath coverage in the future.
DLR Import::2019-04-03